Cancer literacy and its effect on cancer screening behavior of adults of Kaski district, Nepal. - Koirala,Reecha
ABSTRACT: BACKGROUND: Cancer Screening is a key approach to reduce cancer mortality globally and limited Cancer Literacy may pose a barrier to patient engagement in getting screened for cancer. This study was thus conducted to measure the Cancer Literacy level, identify any relationship between Cancer Literacy and Cancer Screening behavior, and identify other factors associated with Cancer Screening behavior among adults of Kaski district of Gandaki Province, Nepal. METHODOLOGY: A cross-sectional study was carried out among 180 adults selected using a random sampling method with multiple stages. Data were collected using a semi-structured questionnaire, with the aid of face-to-face interviews. RESULTS: Among 180 participants, more than half (57.8%) of respondents had limited Cancer Literacy and only 11.7% had ever gone through any Cancer Screening test. After adjusting confounders, Age (p = 0.029), Gender (p = 0.006) and Family Support (p = 0.005) were found to be significant predictors of Cancer Screening behavior among the study participants. CONCLUSION: The findings from this study can be used to tailor cancer awareness campaigns to boost Cancer Screening behavior among the general population. Further research on this issue may help reduce structural inequalities and increase responsiveness to the health systems. Keywords: Cancer Screening, Cancer Literacy, Nepal.